THE STATUS OF COPYRIGHT HOLDERS IN MAKING ONLINE APPLICATIONS ACCORDING TO SHARIA ECONOMIC LAW - Mesi Nadiaturrahmi (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
This article discusses and analyses in depth the status of copyright holders of online application creation according to Sharia economic law. This study aims to analyse the juridical review of the status of copyright holders in the creation of online applications, Islamic law review, and the consequences of ownership. The approach of this research is conceptual and statutory, with a normative juridical perspective, drawing on data obtained from legal materials and prescriptive analysis. The research results show that, from a juridical point of view, Law Number 28 of 2014 concerning Copyright (UUHC) grants the creator-provider the ideal status of copyright holders in the creation of online applications, not the user. The creator is positioned as the original creator of the application, despite the user's contribution. However, if the creator-provider consciously grants a license to the user-contributor, the user becomes the copyright holder, even though this does not eliminate the original rights attached to the creator. Second, in Sharia economic review, online applications can become property rights, namely through direct creation by the creator, or through the process of bai' (sale and purchase), grants, and inheritance. For users, their status is only as owners if the Bai, grant, and inheritance contracts have been completed. The status of the user can be upgraded to a copyright holder if it gets a license or written permission from the original creator. The copyright holder is given to the creator personally or on behalf of the co-creator of the milk musytarak category. In terms of ownership (milkiyyah), everyone can have an online application, either owned by the creator because he created it, or other people through the process of buying and selling (bai'), grants, or inheritance.